PENGARUH BUDAYA DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PERAWAT RUMAH SAKIT LANCANG KUNING PEKANBARU - Damaris Agustina; Kasmirudin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Organizational Citizenship Behavior is not only do the principal work, but also jobs that are outside the main job. Organizational Citizenship Behavior can be influenced by organizational culture and organizational commitment. This study aims to determine the influence of organizational culture and organizational commitment on Organizational Citizenship Behavior nurse the hospital Lancang Kuning Pekanbaru.The method used in this research is descriptive and analytical techniques used are quantitative analysis. The sampling technique used is the census method with a population equal to the number of respondents that amounted to 86 respondents. The data measured with Likert scale. And the data processes by using SPSS 20 program.The results of this study showed organizational culture and organizational commitment positive and significant impact on Organizational Citizenship Behavior nurse the hospital Lancang Kuning Pekanbaru.Keywords:Organizational Culture, Organizational Commitment, and Organizational Citizenship BehaviorKata Kunci: Budaya Organisasi, Komitmen Organisasi, Organizatinal Citizenship Behavior